The implementation of PeSACCS (Peer and Self-Assessment for Collaboration and Communication Skills) in Experimental Class - Muhajir, Siti Nurdianti; Irvani, Asep Irvan; Mulvia, Rahmadhani; Fitriyani, Fitriyani; Lestari, Rahma Tiara (WaPFi (Wahana Pendidikan Fisika), 2025)
This century, education aims to prepare students with the skills needed to thrive in Society 5.0. This has become the basis for ensuring comprehensive, impartial, quality learning and providing long-term learning opportunities for all. Communication and collaboration are essential skills that students must possess to effectively work in teams, solve problems, and adapt to dynamic environments. This study aims to reveal the communication and collaboration skills profile through peer student assessment and laboratory activity self-assessment. This research employs a case study method to analyze the differences between self-assessment, peer assessment, and lecturer observation in practical activities. The subject of this research is fifth-semester physics education students who take the Physics Experiment course. Before the laboratory activity begins, students are divided into small groups. Students are given an observation questionnaire at the end of each class to assess themselves and their group mates. In addition to self-assessments and peer-assessments, the results of the lecturer's observations are also one of the data to provide more in-depth information on students' collaboration and communication abilities.